A comparative case study on seismic design of tall RC frame‐core‐tube structures in China and USA. (22nd January 2015) - Lu, Xinzheng; Li, Mengke; Guan, Hong; Lu, Xiao; Ye, Lieping
Summary To evaluate the major differences between the Chinese and the United States (US) seismic design codes from a structural system viewpoint, a comparative case study is conducted on a tall frame‐core‐tube building, a typical type of reinforced concrete system widely constructed in both countries. The building, originally designed using the US seismic design code, is firstly redesigned according to the Chinese seismic design code based on the information provided by the Pacific Earthquake Engineering Research Center. Secondly, the member dimensions, the dynamic characteristics, the seismic design forces and the material consumptions of the two designs are compared in some detail. Subsequently, nonlinear finite element models of both designs are established to evaluate their seismic performances under different earthquake intensities. Results indicate that the seismic design forces determined by the Chinese response spectrum are larger than those determined by the US spectrum at the same seismic hazard level. In addition, the upper‐bound restriction for the inter‐story drift ratio is more rigorously specified by the Chinese code. These two aspects have led to a higher level of material consumption for a structure designed by the Chinese code. Despite of the above discussions, the two designs yield roughly similar structural performances under earthquakes. Copyright © 2015 John Wiley & Sons, Ltd.